TiO2-Nanobelt-Enhanced, Phosphorescent, Organic Light-Emitting Diodes - Sushanta Lenka; Shivam Gupta; Bushra Rehman; Deepak Kumar Dubey; Hsuan-Min Wang; Ankit Sharma; Jayachandran Jayakumar; Ching-Wu Wang; Nyan-Hwa Tai; Saulius Grigalevicius; Jwo-Huei Jou (Nanomaterials)
This study investigates the enhancement of organic light-emitting diode (OLED) performance through the integration of titanium dioxide (TiO2) nanocomposites within a poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT/PSS) matrix. The nanocomposite films were prepared using a controlled dispersion of TiO2 belts into the PEDOT/PSS solution, followed by their incorporation into the OLED hole-injection layer (HIL). Our results demonstrate a significant improvement in device efficiency, attributed to the optimized charge carrier mobility and reduced recombination losses, which were achieved by the presence of TiO2. The nanocomposite hybrid layer enhances light emission efficiency due to its role in modifying surface roughness, promoting better film uniformity, and improving hole injection. The incorporation of TiO2 nanobelts into PEDOT/PSS led to significant efficiency enhancements, yielding a 39% increase in PEmax, a 37% improvement in CEmax, and a remarkable 72% rise in EQEmax compared to the undoped counterpart. This research provides insight into the potential of TiO2 nanocomposites in advancing OLED technology for next-generation display and lighting applications.